A COMPREHENSIVE REVIEW WITH EMPHASIS ON HISTOPATHOLOGICAL EFFECTS - Rubala Nancy J,; Anto Suganya R,; M Sudha,; L Ashwini,; S.C. Subha, (The Bioscan, 2025)
Biopesticides offer a sustainable and eco-friendly alternative to conventional chemical pesticides, with the potential to reduce resistance in insect populations. As environmental concerns and pesticide resistance rise, there is growing scientific and industrial interest in the discovery and development of novel bioinsecticides. These biocontrol agents are being increasingly integrated, rotated, or combined within pest management programs as part of ecologically sound practices. Current market trends indicate a 15% annual growth in the biopesticide sector, reflecting the global shift toward environmentally conscious agricultural solutions. This trajectory aligns with the principles of Integrated Pest Management (IPM), promoting reduced chemical dependency. Recent research has expanded the use of microbial agents, particularly novel bacterial species, as effective alternatives to synthetic insecticides. Histopathological studies play a critical role in understanding the mode of action and safety of these biopesticides on target and non-target organisms.